Low educational level but not low income impairs the achievement of cytogenetic remission in chronic myeloid leukemia patients treated with imatinib in brazil - Metze, Konradin, 1956- (2015)
In Brazil, imatinib mesylate is supplied as the first-line therapy for chronic myeloid leukemia in the chronic phase through the public universal healthcare program, Sistema U´ nico de Sau´ de (SUS). We studied the socio-demographic factors that influence